Formulation and Evaluation of Transdermal Patch of Stavudine - Kumar, Sahoo Sunit; Behury, Baurahari; Sachinkumar, Patil (Dhaka University Journal of Pharmaceutical Sciences, 2013)
Stavudine has the half life of 1 to 1.5 hour and bioavailability in the body is 86% due to first-pass metabolism. The dose of stavudine is 40 mg two to three times daily depending on weight and gender; hence, it requires frequent dosing. Transdermal patch of stavudine was prepared to sustain the release and improve bioavailability of drug and patient compliance. Different formulations were prepared by using different concentrations of Eudragit RS 100 and Eudragit RL 100. The prepared formulations were evaluated for various parameters like weight, thickness, drug content, percentage moisture content, percentage moisture uptake, tensile strength, folding endurance, In vitro drug release and in vitro permeation studies. Also these patches were characterized by Field Emission Scanning Electron Microscopy and Fourier transforms Infrared Spectrosphotometry (FTIR). All formulations have shown 0 % constriction of the patches indicating 100% flatness of the transdermal patches. Thus, these formulations can maintain a smooth and uniform surface when they are functional onto skin. The folding endurance values of patches showed optimum flexibility of the patches. The moisture content and moisture uptake in the formulations of transdermal patch was found to be increased by increase in the concentration of Eudragit RS 100 and decreasing the concentration of Eudragit RL 100. FTIR study has shown absence of any interaction of the drug with the excipients. As concentration of Eudragit RL100 increased and subsequently the concentration of Eudragit RS100 decreased, the drug release was enhanced. Dhaka Univ. J. Pharm. Sci. 12(1): 63-69, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16302